2013
DOI: 10.3389/fncel.2013.00039
|View full text |Cite
|
Sign up to set email alerts
|

D-serine as a gliotransmitter and its roles in brain development and disease

Abstract: The development of new techniques to study glial cells has revealed that they are active participants in the development of functional neuronal circuits. Calcium imaging studies demonstrate that glial cells actively sense and respond to neuronal activity. Glial cells can produce and release neurotransmitter-like molecules, referred to as gliotransmitters, that can in turn influence the activity of neurons and other glia. One putative gliotransmitter, D-serine is believed to be an endogenous co-agonist for syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 160 publications
(210 reference statements)
0
54
0
Order By: Relevance
“…In addition to glutamate, NMDAR activation, i.e., channel opening, requires the binding of a coagonist, initially thought to be glycine (Johnson and Ascher, 1987; Kleckner and Dingledine, 1988; Figure 1 ). However, many studies during the last 15 years have shown that D -serine, an unusual amino acid synthesized in the brain by serine racemase (SR; Campanini et al, 2013) and degraded by the peroxysomal flavoprotein D -amino acid oxidase (DAAO; Sacchi et al, 2012), is the main coagonist of synaptic NMDARs in various brain areas (Martineau et al, 2006; Wolosker, 2011; Billard, 2012; Van Horn et al, 2013). Accordingly, D -serine is a physiological modulator of many NMDAR-dependent functions, including brain development (Kim et al, 2005), synaptic transmission and long-term synaptic plasticity ( Figure 1 ; Mothet et al, 2000; Yang et al, 2003; Papouin et al, 2012; Li et al, 2013; Rosenberg et al, 2013), as well as learning, memory, and social interactions (Labrie et al, 2008; DeVito et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to glutamate, NMDAR activation, i.e., channel opening, requires the binding of a coagonist, initially thought to be glycine (Johnson and Ascher, 1987; Kleckner and Dingledine, 1988; Figure 1 ). However, many studies during the last 15 years have shown that D -serine, an unusual amino acid synthesized in the brain by serine racemase (SR; Campanini et al, 2013) and degraded by the peroxysomal flavoprotein D -amino acid oxidase (DAAO; Sacchi et al, 2012), is the main coagonist of synaptic NMDARs in various brain areas (Martineau et al, 2006; Wolosker, 2011; Billard, 2012; Van Horn et al, 2013). Accordingly, D -serine is a physiological modulator of many NMDAR-dependent functions, including brain development (Kim et al, 2005), synaptic transmission and long-term synaptic plasticity ( Figure 1 ; Mothet et al, 2000; Yang et al, 2003; Papouin et al, 2012; Li et al, 2013; Rosenberg et al, 2013), as well as learning, memory, and social interactions (Labrie et al, 2008; DeVito et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A CLEC method enabling the separation of serine enantiomers can be of practical relevance in the case of analysis of brain samples or cerebrospinal fluids. Indeed, it is widely known that the (S)-serine is involved in several pathophysiological central nervous system (CNS) states (Van Horn et al, 2013;Xia and Xiong, 2013).…”
Section: Modified (R)-stc-based C-cspmentioning
confidence: 98%
“…However, in these studies, the transmitter substance(s) released during gliotransmission are uncertain. Gliotransmission can involve the vesicular release of excitatory transmitters, including glutamate, serine, and adenosine triphosphate (ATP) (Pascual et al, 2005; D’Ascenzo et al, 2007; Parpura & Zorec, 2010; Santello, Cali, & Bezzi, 2012; Martineau, 2013; Van Horn, Sild, & Ruthazer, 2013). Of these, glutamate appears to contribute to drug-seeking behavior and other aspects of cocaine addiction (Beardsley & Hauser, 2014)…”
Section: Astrogliamentioning
confidence: 99%